Redating the Zhuwobu Paleolithic site in the Huailai basin, North China, using the MET-pIRIR procedure on K-feldspars - GUO, Yujie; XIAN, Qi; LU, Chun; NIU, Dongwei (Frontiers in Earth Science, 2022)
As part of the ‘generalized Nihewan Basin’, the Huailai basin has recently attracted archaeologists’ attention. Ten Paleolithic sites were found in this basin in 2014; among these, the Zhuwobu site is the oldest―dated to 504 ± 76 ka using the electron spin resonance (ESR) dating method. This paper redated the Zhuwobu site using the multiple elevated temperatures (MET) post infrared (pIR) infrared stimulated luminescence (IRSL) procedure (MET-pIRIR) on both multi-grained single and multiple aliquots of potassium-rich feldspars (K-feldspars). The consistency of the De results obtained from the single- and multiple-aliquot procedures mutually supported the reliability of our age results. Our results suggest that the cultural layer at this site was deposited about 280 ± 13 ka (MIS 8) ago, ~220 ka younger than the previous ESR age. Considering the region’s tectonic history and the characteristics of the sedimentary facies for the ZWB site, we suggested that the previous ESR age results for the bottom three samples from the sediment profile might be overestimated due to poor bleaching before burial. In contrast, the ESR age of 346 ± 32 ka (MIS 10) for one cultural-layer collected sample might be more reliable due to higher-quality bleaching before burial. Further archaeological, geological, and chronological studies are needed to explore the ancient hominins’ survival conditions in the ‘generalized Nihewan’ Basin and possible connections with the renowned Zhoukoudian sites.